2007
DOI: 10.1080/00365520701452225
|View full text |Cite
|
Sign up to set email alerts
|

Elevated B cell-activating factor of the tumour necrosis factor family in coeliac disease

Abstract: BAFF may represent a possible pathogenic factor in CD. Its implications for the diagnosis, prognosis and treatment of CD should also be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 42 publications
2
31
1
2
Order By: Relevance
“…Fabris et al [13] reported elevated BAFF plasma levels in a small cohort of patients with coeliac disease, and concluded that BAFF might play a pathogenic role in its development. Jee et al [14] observed a relationship between food allergens and BAFF levels in a cohort of children with atopic dermatitis, suggesting that food allergens are more important for atopic dermatitis development than are aeroallergens; however, dietary composition was not investigated in their study.…”
Section: Introductionmentioning
confidence: 99%
“…Fabris et al [13] reported elevated BAFF plasma levels in a small cohort of patients with coeliac disease, and concluded that BAFF might play a pathogenic role in its development. Jee et al [14] observed a relationship between food allergens and BAFF levels in a cohort of children with atopic dermatitis, suggesting that food allergens are more important for atopic dermatitis development than are aeroallergens; however, dietary composition was not investigated in their study.…”
Section: Introductionmentioning
confidence: 99%
“…1 Interestingly, the up-regulation of a growth factor required for B-cell proliferation, BLyS (B lymphocyte stimulator), has been shown by our group to be highly expressed in both MC and CD. 7,8 In MC syndrome and associated indolent lymphomas the elimination of the viral infection may ameliorate disease and be accompanied by morphologic neoplastic regression in some cases. 9,10 The biologic characteristics of MC syndrome are then of extreme importance for the study of the etiopathogenetic mechanisms linking antigen stimulation to autoimmunity and to lymphoproliferation.…”
mentioning
confidence: 99%
“…Statistically significant correlation between TNF-␣ and IgA-anti-tTG, as shown in our work, might suggest that TNF-␣ is among major factors responsible for damage to the small intestine epithelium and increase in tTG secretion (20). Recently, a few studies were published on the role of antibodies against tTG (anti-tTG) in celiac disease diagnosis (21).…”
Section: Discussionmentioning
confidence: 97%